2020
DOI: 10.1371/journal.pgen.1008830
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish rbm8a and magoh mutants reveal EJC developmental functions and new 3′UTR intron-containing NMD targets

Abstract: Many post-transcriptional mechanisms operate via mRNA 3 0 UTRs to regulate protein expression, and such controls are crucial for development. We show that homozygous mutations in two zebrafish exon junction complex (EJC) core genes rbm8a and magoh leads to muscle disorganization, neural cell death, and motor neuron outgrowth defects, as well as dysregulation of mRNAs subjected to nonsense-mediated mRNA decay (NMD) due to translation termination � 50 nts upstream of the last exon-exon junction. Intriguingly, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 101 publications
6
19
0
Order By: Relevance
“…Rbm8a haploinsufficiency impairs mouse cortical development due to reduced numbers of progenitors and neurons and the perturbation of cortical lamination ( Mao et al., 2015 ). Morpholino-mediated knockdown of rbm8a in Danio rerio results in disorganized myofibers and motor axon outgrowth defects ( Gangras et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rbm8a haploinsufficiency impairs mouse cortical development due to reduced numbers of progenitors and neurons and the perturbation of cortical lamination ( Mao et al., 2015 ). Morpholino-mediated knockdown of rbm8a in Danio rerio results in disorganized myofibers and motor axon outgrowth defects ( Gangras et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the conditional haploinsufficiency of Eif4a3, Y14 (Rbm8a) or Magoh induces apoptosis and p53 ablation rescues apoptosis in the three EJC mutants (Mao et al, 2016). In addition, loss of Y14 (rbma8) or magoh in zebrafish also leads to the apoptotic phenotype as eif4a3 mutant embryos and morphant embryos (Gangras et al, 2020). Therefore, these data suggested that the apoptosis is likely due to the impairment of the EJC complex.…”
Section: Discussionmentioning
confidence: 92%
“…RBM8A is a core component of the exon junction complex (EJC), through which it contributes to the formation and development of the nervous system (McSweeney et al, 2020). RBM8A deficiency leads to muscle disorganization, neuronal cell death, and motor neuron growth defects (Gangras et al, 2020); conversely, increased RBM8A expression leads to increased proliferation of cells in the ventricular and subventricular zones, while decreasing the migration of cells toward the cortical plate (Zou et al, 2015). Differential expression and dysfunction of EJC core proteins have been reported in multiple cancers (Degot et al, 2004;Kahles et al, 2018;Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%